(untitled) (Research, Society and Development, 2020)
Diabetes mellitus is a chronic disease that affects millions of people around the world. One of the medicinal plants used by the Brazilian population in the treatment of diabetes mellitus is Bauhinia forficata Link. The objective of this work was to conduct a review of clinical case studies in order to analyze the hypoglycemic effect of B. forficata infusion in diabetic and pre-diabetic individuals. A direct search for articles of clinical cases was carried out in the databases LILACS, PubMed, SciELO, and Scopus. Were searched works in Spanish, English and Portuguese, published in the last 10 years and that only used the infusion of leaves of the plant species in the treatment of mens and womens, over the age of 18, with pre-diabetes or diabetes mellitus. Were used the keywords "Bauhinia forficata" and "diabetes", and the boolean operator “AND”. Five studies were found, of which three of them presented positive results in relation to the use of B. forficata infusion as an effective hypoglycemic agent in diabetic and pre-diabetic individuals, while two studies did not present positive results. It was concluded that the infusion of B. forficata is able to assist in the treatment of diabetes mellitus, despite the need for more scientific evidence on the subject.